2015
DOI: 10.1016/j.jclepro.2015.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Assessing sustainability and value of manufacturing processes: a case in the aerospace industry

Abstract: a b s t r a c tIn spite of the growing awareness and significance of accounting for sustainability aspects in product development, design decision support is still immature in this end compared to other decision support areas, such as product performance and manufacturability. This paper proposes a novel decision support method that combines qualitative sustainability assessment techniques with a quantitative analysis, without losing transparency and still covering a full sustainability perspective. The aim is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 44 publications
0
39
0
2
Order By: Relevance
“…While some aspects of sustainability are partially encompassed by the established drivers for product or service innovation (e.g., specific fuel consumption, lifetime and weight reduction in the automotive and aerospace industry), others are less readily quantifiable (e.g., material criticality from an availability and socio-ecological sustainability perspective) and problematic to use as criteria for decision making [9,10].…”
Section: Introduction and Objectivesmentioning
confidence: 99%
“…While some aspects of sustainability are partially encompassed by the established drivers for product or service innovation (e.g., specific fuel consumption, lifetime and weight reduction in the automotive and aerospace industry), others are less readily quantifiable (e.g., material criticality from an availability and socio-ecological sustainability perspective) and problematic to use as criteria for decision making [9,10].…”
Section: Introduction and Objectivesmentioning
confidence: 99%
“…A case study in which ecological footprint was combined with environmental risk assessment was presented by Herva et al (2011). Hallstedt et al (2015) introduced the sustainability assessment and value evaluation (SAVE) method, which combines a strategic sustainability assessment with net present value analysis, based on scenarios. Gargalo et al (2016) suggested a multi-level framework for techno-economic and environmental sustainability analysis through risk assessment to be used in early product development.…”
Section: Literature Review Results: State Of the Artmentioning
confidence: 99%
“…In a similar approach, Sustainability Assessment and Value Evaluation method (SAVE), qualitative sustainability assessment techniques including sustainability guided questions are combined with quantitative Net Present Value (NPV) analysis. The method allocates sustainability hotspots and clarifies potential sustainability consequences of a new concept (Hallstedt et al, 2015). The SAVE method can support a design team to build NPV scenarios based on possible changes for some identified sustainability parameters.…”
Section: Methodsmentioning
confidence: 99%